Determinant of Customer Churn in the Nepalese Mobile Telephony Market (Management Dynamics, 2022)
This study aims to trace the primary reason for discontinuing the service or switching to other telecom operators by the customers. This study examines the customer churn determinant in the Nepalese mobile telephony market. The study used descriptive statistics and causal research design, i.e., a multiple linear regression model with 400 samples collected through a structured questionnaire. The study found that pricing and tariff, network quality, customer service and support, and new product and services are major determinants of customer churn in the Nepalese mobile telephone market. The current study is useful for developing predictive modeling by telecom operators to tap the possible churner beforehand by taking necessary marketing initiatives. Further, the study outcome could be useful for regulation in terms of devising the policy related to product offering by Nepalese telecom, pricing of the service, and the need to monitor the service quality by the telecom operators.